Study of HACCP (Hazard Analysis And Critical Control Point) identification in anchovy sago noodles processing - Surahman Diki Nanang; Cahyadi Wisnu; Alifia Maisa Hamdu Nurani; Litaay Christina; Astro Hendarwin M.; Rahman Taufik (BIO Web of Conferences, 2024)
Noodles are a practical food product that the people of Indonesia love. Many efforts to diversify noodle products by substituting non-gluten ingredients such as sago. The pilot plant of the Research Center for Appropriate Technology, Subang is one of the models for processing sago flour into dry noodle products fortified with anchovy flour. In its operation, it is necessary to apply the HACCP system. The HACCP identification study was conducted using the HACCP Plan Preparation Guide, with its preparation following the principles of the HACCP system recommended by the Codex Alimentarius Commission and Indonesian National Standards. The results of the study showed that the process stages set as CCP in the manufacture of anchovy flour is drying. In addition, the process stages set as CCP in making anchovy sago noodles is tempering. All of these CCPs must receive optimal supervision including adequate temperature and drying time of fish and environmental humidity.